SISTEM INFORMASI PEMESANAN PEMENTASAN SENI TARI BERBASIS WEBSITE STUDI KASUS SANGGAR CANGGET BUDAYA KOTABUMI LAMPUNG UTARA - Rima Mawarn; Intan Oktaria; Rianda Venia Audina (STMIK Dian Cipta Cendikia Kotabumi, 2018)
ABSTRACTSanggar Cangget Culture is an organization engaged in the art of dance.To provide a better service and the latest information to customers, its products are in need of a system that can be accessed by customers from anywhere.This system will make it easier for customers to obtain information or obtain a service.As for development used in this research is the Object Oriented model using several tools such as Use Case, Activity Diagrams, Class diagrams and Squence Diagram.And for system development method that is used is the method Prototype/Prototyping.The method Prototype/Prototyping is the sequence of activities that started from the collection needs, build a prototyping, prototyping, evaluation, test systems encode system, evaluation system and the use of the system.Expected by the existing Systems of information Ordering Performances Dance Studio Case Study-based websites Cangget Kotabumi North Lampung Culture makes it easy for users to order dance anywhere over the internet and can be connected to improve the performance and quality of service.